Letter - Jourdain, Francis, 1876-1958
016b-0022-001 COMITÉ MONDIAL CONTRE LA GUERRE ET LE FASCISME Weltkomitee gegen Krieg und Faschismus — World Committee against War and Fascism Fondateur : HENRI BARBUSSE President d'honneur : ROMAIN ROLLAND Secretaire general : FRANCIS JOURDAIN Conseil de Présidence - France : Paul LANGEVIN, Jean LONGUET, Andre MALRAUX Angleterre: Sir Norman ANGELL Allemagne : Heinrich MANN Etats-Unis : H.-F. WARD, Sherwood ANDERSON, John dos PASSOS Canada : A.-A. MACLEOD November 2 1937. Dear Friend, November 7 marks the first anniversary of the attack launched by Franco against the capital of Spain, an attack which he boasted would assure his forces a speedy and conclusive victory. On the 7th of November, therefore, the open city of Madrid will have shown the world throughout a whole year a heroic resistance which neither bombardment nor aerial attack has been able to overcome. If in the North of Spain the fascists have gained successes, these have been entirely due to the overwhelming and incessant Italian and German intervention. At this critical hour we feel that all who support the cause of peace and freedom will desire to put on record their recognition of the heroism displayed by the defenders of Madrid and take the opportunity to state their views on the war itself, so fraught with incalculable dangers for the peace of Europe and the world. Such declarations have a special importance at the present moment owing to the fact that the vital questions of non-intervention, of the withdrawal of foreign troops, and of the application of the Commercial Treaty of September 1935 and opening of the French frontier, which has been so long closed while the fascist powers have, with impunity, been allowed to give the most effective aid to Franco, are just now undergoing critical consideration. Further, we are certain that you are conscious of the responsibility which falls on all the democratic peoples in regard to the hundreds of thousands of men, women and children who can still be saved from massacre and distress. We therefore hope that you will be so good as to send us a statement of your views on this occasion of the anniversary of the attack on Madrid. We shall take steps to secure publicity for such statements in all countries, as in the case of the statements received on the anniversary of July 18, and we are sure that they will exert an important influence, especially in Spain, where your declaration will afford valuable encouragement to our friends. Yours sincerely, Francis Jourdain 38, boulevard Raspail, PARIS-7e Francis JOURDAIN, Chéque postal Paris 1288-83 Téléph. LITTRÉ 38-45, 38-46 Adresse télégraphique : MOUVEDIAL-PARIS 292/946/16b/25